Efficient and Lightweight Link Discovery Protocol (ELDP) for Software Defined Network - Aladesote, Olomi Isaiah; Azizol, Abdullah; Normalia, Samian; Mohd. Hanapi, Zurina (Applied Information Technology And Computer Science, 2024)
The paradigm shift in the network industry correlates with the limitations of traditional networks, such as inconsistent regulations, vendor dependencies, complexity, and scalability issues. Software-defined network (SDN) addresses these issues with a novel architecture that uses a controller for efficient resource allocation. However, the existing OpenFlow Discovery Protocol (OFDP) is inefficient, requiring multiple messages to detect links. This study proposes an Efficient and Lightweight Topology Discovery (ELDP) to overcome these limitations. ELDP involves the controller sending a single packet-in to a switch, which then distributes it to other switches, mapping adjacent switches connected to its ports and Short Switch Chase ID (SSCID). This optimizes the link discovery process. Experimental results show a significant reduction of 50% to 93.45% in the number of messages required for discovery, validating the effectiveness of ELDP in SDN environments.